All Days 2010
DOI: 10.2118/128074-ms
|View full text |Cite
|
Sign up to set email alerts
|

When Do Surfactant-Based Acids Work as Diverting Agents?

Abstract: The purpose of matrix stimulation in carbonate reservoirs is to bypass the damaged zones and increase the effective wellbore area. This can be achieved by creating highly conductive flow channels known as wormholes. A further injection of acid will follow the wormhole path where the permeability has increased significantly, leaving substantial intervals untreated. This problem can be significant as the contrast in permeability increases within the target zones. Diverting materials such as surfactant-based acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The diversion ability was evidenced by the increase in the down hole pressure during the injection of the diverter and the change in bottom hole injection temperature. Extensive laboratory experiments were conducted by Al-Ghamdi et al to evaluate the efficiency of VES-based HCl in carbonate stimulation using a parallel coreflooding system. They showed that, when straight 15 wt % HCl was used, the acid flowed through the high permeability cores and created dominant wormholes and did not break through the low permeability cores. They tested the VES-based HCl acid system and they showed that it was effective in diverting the acid flow in permeability contrast (ratio of high permeability to low permeability rocks).…”
Section: Application Of Nps In Surfactant and Polymer-based Stimulationmentioning
confidence: 99%
“…The diversion ability was evidenced by the increase in the down hole pressure during the injection of the diverter and the change in bottom hole injection temperature. Extensive laboratory experiments were conducted by Al-Ghamdi et al to evaluate the efficiency of VES-based HCl in carbonate stimulation using a parallel coreflooding system. They showed that, when straight 15 wt % HCl was used, the acid flowed through the high permeability cores and created dominant wormholes and did not break through the low permeability cores. They tested the VES-based HCl acid system and they showed that it was effective in diverting the acid flow in permeability contrast (ratio of high permeability to low permeability rocks).…”
Section: Application Of Nps In Surfactant and Polymer-based Stimulationmentioning
confidence: 99%
“…13 Al-Ghamdi et al found through experimental research that achieving better diverting efficiency is closely related to the injection displacement of diverting acid and, based on experimental data, established an analytical model for the velocity distribution of flow inside wormholes and the optimal displacement. 14 Liu et al further conducted 3D wormhole expansion research under linear flow conditions, and according to the minimum resistance seepage principle, in reservoirs containing karst caves and fractures, acid solution is more inclined to flow into such media, believed to be because large-scale karst caves and fractures are key actors affecting wormhole development. 15 Liu et al established a mathematical model to describe the VES diverting behavior through experiments, and the simulation results confirmed that the diverting behavior depends on the residual acid area and the viscosity of the residual acid.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent past, several studies attested the efficacy of VES-based system as acid diverters (Al-Ghamdi et al, 2010;Gomaa et al, 2012;Yu et al, 2010). Chang et al have reported the use of carboxybetain VES as selfdiverting acid systems, which successfully diverted acid from high-permeability core into the low-permeability core (Al-Ghamdi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%